Geminiviruses encode additional small proteins with specific subcellular localizations and virulence function - Pan Gong (Nature Portfolio, 2021)
Geminiviruses are small plant-infecting viruses. Here the authors screen the geminivirus genome for small open reading frames that may have been previously overlooked and show that one encodes a protein named V3 that localizes to the Golgi and acts as an RNA silencing suppressor.